Công bố và minh bạch thông tin với kết quả kinh doanh của doanh nghiệp niêm yết ởViệt Nam - Le Quang , Canh; Nguyen Vu , Hung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This paper investigates whether information disclosure matters to the performance of listed firms in Vietnam with a focus on transparency/quality of information disclosed. From the regression techniques applied to a sample of 354 firms listed on the Hanoi Stock Exchange, our empirical results show that more information disclosure is related to lower firm performance as proxied by ROA and Tobin’s Q (TOQ). This research contributes to the literature by adding new empirical evidence and unique explanation of the reversed relationship between information disclosure and firm performance. It thus confirms the importance of timeliness and accessibility aspects of information disclosure when studying its impact on the performance of those listed firms in Vietnam.
Keywords: Information disclosure and transparency; corporate governance; firm performance